Maybe "I Do, " Maybe I Don't: Respectability Politics in the Same‐Sex Marriage Ruling. Issue 1 (28th October 2015) - Matsick, Jes L.; Conley, Terri D.
Abstract : Frost and Gola (2015) offer empirical evidence that same‐sex and different‐sex relationship partners are similar in their experiences of intimacy and, as a result, the meaning of marriage will not fundamentally change with the legalization of same‐sex marriage. In this commentary, we offer another perspective: given the unique aspects of same‐sex relationships, we argue that the meaning of marriage may indeed change as same‐sex partners legally wed. We extend Frost and Gola (2015) by considering the limitations of respectability politics when advocating for same‐sex relationships and by shedding light on those who may seek to change the meaning of marriage.